Pemikiran Pendidikan Islam al-Zarnuzi: Analisis Kritis Penghormatan Terhadap Ilmu dan Guru - Khairuni, Nisa (Tadabbur: Jurnal Peradaban Islam, 2021)
A person's moral is reflected in morals. This can be obtained from education, especially Islamic education as al-Zarnuzi's thought is known for his moral messages in his Ta'lim al Muta'allim work, but so far many students have found failures in terms of moral competence, then this paper is discussed using library research that is by searching to collect, read and analyze the research problem in the books. The findings show that learning must intend and have a goal to seek the pleasure of Allah, written, repeated lessons that have been learned, deliberation, Taammul. In addition, al-Zarnuzi also explained some of the requirements in seeking knowledge in order to succeed. The students must be smart, have high curiosity, be patient, have money, listen to the instructions from the teacher, and have time to study. Furthermore, when viewed from the area of ​​time setting and the place where Shaykh al-Zarnuji lived, distance and time stretch between the past and the present. The problem that may occur today that it can be called weakness is that the instruments and tools used to develop education certainly cannot be applied just like that in the present. One example is the role and behavior of respecting teachers. If what al-Zarnuji says is explained exclusively, what ultimately happens is unconditional obedience. This is where future education will lose its significance. So a possible weakness arising from al-Zarnuzi's thought is a textual understanding of his work.